Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Sepatu Brand X-Fourth Di E-Commerce Shopee - Nashr Maulana Hamada; Sinta Sulistiani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of product quality and price on purchasing decisions for X-Fourth Brand Shoes on Shopee E-Commerce. The research method used is quantitative by distributing questionnaires to 97 respondents. Data analysis was carried out using validity, reliability, classical assumptions, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results of the study indicate that Product Quality has a significant effect on Purchasing Decisions with a calculated t-value of 5.516 and a significance of 0.001 <0.05. Price also has a significant effect on consumer satisfaction with a calculated t-value of 2.757 and a significance of 0.007 <0.05. Simultaneously, product quality and price have a significant effect on Purchasing Decisions with a calculated F-value of 22.534 and a significance of 0.001 <0.05. The coefficient of determination (R²) of 0.305 indicates that 30.5% of the variation in Purchasing Decisions can be explained by product quality and price. Thus, effective quality and good price have been proven to be important factors in improving purchasing decisions. The research concluded that purchasing decisions have a positive and significant effect on purchase satisfaction, and price has a positive and significant effect on purchasing decisions. The conclusion is that the X-Fourth shoe brand should improve its pricing strategy to significantly increase sales and revenue